A retrospective study on prevalence of hyperuricemia in patients with hypertension and type 2 diabetes mellitus (T2DM) from a teaching hospital of west Uttar Pradesh, India - Datta, Debranjan; Giri, Vishal Prakash (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Hyperuricemia have been associated with an increased risk for not only type 2 diabetes mellitus (T2DM) and hypertension but also for metabolic syndrome, hyperinsulinemia, gout and many cardiovascular diseases. The objective of the present study was to determine the prevalence of hyperuricemia in patients with hypertension and / or type 2 diabetes mellitus patients from a teaching hospitals of West Uttar Pradesh. Methods: A retrospective study was carried out in the department of pharmacology, Teerthanker Mahaveer Medical College and Research centre, Moradabad, West Uttar Pradesh over a period of six months. Results: A total of 524 case records with high blood pressure and / or type 2 diabetes mellitus were examined during the study period. The mean age of subjects reported was 45 years. A 35.3 % (185/524) were found to have elevated serum uric acid level. The prevalence of hyperuricemia was found increased with an increased duration of disease among hypertensive, diabetic patients. Conclusions: A high prevalence of hyperuricemia was observed among patients with hypertension, type 2 diabetes mellitus and among the patients with both co-morbidities in our studies.